(untitled) - Whitted, Gary S. (New York, NY, USA, 1985)
Part 1: background; Part II: initiating a health care expense managemant program; Part III: specific expense management strategies
Keywords: Bảo hiểm sức khỏe,Health insurance; Quản lý,Management